ABSTRACT Production scheduling is an important aspect to support the success of a manufacturing company in achieving the target of production planning and affects the implementation of the production process over a period of time. The amount of idle time in scheduling are considered less effective in the production line and detailed production scheduling becomes a problem to be solved with rearrangment of the daily activities in PT. MDS. Modeling proper scheduling is a means to help develop the - Agus Hidayatul Rohman dan Taufik Djatna (E-jurnal Agro-Industri Indonesia, 2012)
ABSTRACT Production scheduling is an important aspect to support the success of a manufacturing company in achieving the target of production planning and affects the implementation of the production process over a period of time. The amount of idle time in scheduling are considered less effective in the production line and detailed production scheduling becomes a problem to be solved with rearrangment of the daily activities in PT. MDS. Modeling proper scheduling is a means to help develop the daily production schedule. Preliminary research results indicate that modeling of production scheduling in PT. MDS are influenced by demand  of products, stock products, number of production, downtime of machine cause of change over time, the order of production  scheduling, transportation delay between machines, and working time of machine. The selection of the method of calculation in the preparation of scheduling models must be adapted to the conditions preliminary research to give solutions of  scheduling problems in PT. MDS. A  Critical ratio method, the next grouping of products, and  re-sequencing of production process with Shortest Processing Time method is the right method to re-sequencing of scheduling models in response to a scheduling problem in PT. MDS. A Critical ratio method is useful to sort the product type, while the grouping of products and the Shortest Processing Time method useful to maximize the use of equipments as well as reducing of idle time. The results showed a decreased machine utilization of 64% to 60% and downtime of machine decreased to 5%.                                                                                                                Key words : utilization of machine, idle time, production sequence, critical ratio, shortest processing time,               productivity